The Activity of Cotinus coggygria Scop. Leaves on Staphylococcus aureus Strains in Planktonic and Biofilm Growth Forms - Katarína Rendeková; Silvia Fialová; Lucia Jánošová; Pavel Mučaji; Lívia Slobodníková (Molecules, 2015)
The purpose of this study was to detect the effectiveness of Cotinus coggygria Scop. leaves methanol extract against planktonic and biofilm growth forms of Staphylococcus aureus. The antimicrobial activity was determined by the broth microdilution test. Minimal inhibitory concentrations and minimal bactericidal concentrations were detected against two collection and ten clinical S. aureus strains. Anti-biofilm activity of the tested extract was detected using 24 h bacterial biofilm on the surface of microtiter plate wells. The biofilm inhibitory activity was evaluated visually after 24 h interaction of extract with biofilm, and the eradicating activity by a regrowth method. The tested extract showed bactericidal activity against all S. aureus strains (methicillin susceptible or methicillin resistant) in concentrations ranging from 0.313 to 0.625 mg·mL−1. Biofilm inhibitory concentrations were 10-times higher and biofilm eradicating concentrations 100-times higher (8 and 32 mg·mL−1, respectively). The phytochemical analysis of C. coggygria leaves 60% methanol extract performed by LC-DAD-MS/MS revealed quercetin rhamnoside, methyl gallate, and methyl trigallate as main constituents. Results of our study indicate that C. coggygria, rich in tannins and flavonoids, seems to be a prospective topical antibacterial agent with anti-biofilm activity.